Galectin-3: a novel antimicrobial host factor identified in goat nasal mucus - Yichao Ma; Xinming Qin; Jiachen Liu; Shiqi Liu; Ruoyang Lin; Baoyan Meng; Xiaojing Cui; Qian Yang (Veterinary Research)
Abstract Respiratory infections caused by pathogenic bacteria pose a rapidly growing public health threat. The nasal mucus layer serves as the first line of defense against pathogen invasion; however, in nasal mucus, the antimicrobial components and their underlying mechanisms remain unclear. Here, we collected nasal mucus from goat nasal mucosal explant models and identified significant antimicrobial activity in the total protein fraction. Subsequent fractionation indicated that proteins < 30 kDa exhibited the most potent bactericidal activity. Nano LC–ESI–MS/MS analysis identified galectin-3 as a key protein with potent activity against Gram-positive bacteria, particularly Streptococcus suis (S. suis). Galectin-3 targeted teichoic acids on the bacterial surface, disrupting membrane integrity. Additionally, it inhibited the synthesis of three critical bacterial proteins: enoyl-ACP reductase (FabK), carbamate kinase (CK), and small ribosomal subunit protein uS2 (rpsB), thereby destroying bacterial growth and metabolism. In the murine nasal infection model, galectin-3 accelerated the clearance of S. suis and alleviated pathological damage caused by the infection. Taken together, our findings provide the first evidence of the direct antimicrobial action of galectin-3 in nasal mucus and elucidate its mechanisms involving bacterial membrane disruption and inhibition of key metabolic proteins. These results highlight galectin-3 as a promising therapeutic target for S. suis infections.